Study on surface quality and accuracy of hard turned axial feed rollers of honing machine. (26th March 2012) - Raju, V.R.; Chellamalai, M.; Kumar, P.V. Shashi
Hard turning process is emerging as an alternative to traditional grinding operations. The advantage of using hard turning is that wheel–dressing operation is eliminated and machining complex contours is less tedious as single point cutting tool is used. Hard turning process of hardened parts (> 45 HRC) has many potential benefits compared to grinding, which remains the standard finishing process for critical hardened surfaces. The objective of hard turning is to remove work piece material in a single cut rather than a lengthy grinding operation, thus reducing processing time and production cost. The wear of the cutting inserts was evaluated and inspected by using optical profiler and SEM. Surface roughness was investigated as a function of the cutting condition for a given geometry of the cutting tool. This paper describes the technology development of axial feed rollers by using hard turning process. The problem faced to achieve the required surface finish, form accuracy, tool wear rate and tool lives are presented in this paper.